Pengaruh kapasitas sumber daya manusia, pemanfaatan teknologi, dan komitmen organisasi terhadap kualitas laporan keuangan di pemerintahan Kota Medan - Br Hombing, Ayu Kristina; Pandiangan, Reggy Reynatasya; Simangunsong, Dona; Malau, Yois Nelsari (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
The purpose of this study was to determine and analyze the effect of human resource capacity, technology utilization, and organizational commitment on the quality of financial reports in the city government of Medan. The research method used is a quantitative approach. The method of analysis used in this study is Multiple Linear Regression. The results of the determination coefficient analysis obtained a value of 0.118, which means that the Variable Variable of Quality of Financial Statements which can be explained by Variable Variations in Human Resource Capacity, Utilization of Technology and Organizational Commitment is 8% while the remaining 92% is explained by other independent variables such as Internal Control, Understanding Accounting Standards The research results show that Simultaneously Human Resources, Technology Utilization, and Organizational Commitment do not have a positive and insignificant effect on the Quality of Partial Financial Statements. Human Resources and Organizational Commitment have no negative and insignificant effect on the Quality of Financial Statements. Technology Utilization Variable Partially has a positive and significant effect on the Quality of Financial Statements.